Czytanie poety – widzenie poezji. O Wojaczku Lecha Majewskiego - Otto, Wojciech (Przestrzenie Teorii, 2019)
Otto Wojciech, Czytanie poety – widzenie poezji. O Wojaczku Lecha Majewskiego [Reading a Poet – Seeing Poetry. On Wojaczek by Lech Majewski]. „Przestrzenie Teorii” 32. Poznań 2019, Adam Mickiewicz University Press, pp. 285–300. ISSN 1644-6763. DOI 10.14746/pt.2019.32.15. The film chronicles the last days in the life of Rafał Wojaczek, who committed suicide at the age of 26. This is the director’s vision that reflects the spirit and character of an artistic genius and his poetic work. Wojaczek is presented against the background of the grey, dirty and bleak communist reality of the late 1960s and early 1970s and therefore becomes a symbol of a rebellious artist, not reconciled with the world and with himself. His colourful character and no less impressive works shown in the film create the image of an artist whose life led in a straight line and with absolute consistency towards self-destruction. By showing the poet’s rebellion against reality, the director describes the artist’s self-destruction that headed for a tragic end. The is a black and white film with many experimental form treatments.